CONCEPTUAL METAPHOR OF SETYA NOVANTO’S CASE - Sintia Purnama; Muhammad Akbar Nurhakim (IKIP Siliwangi, 2018)
This research is entitled Conceptual Metaphors of Setya Novanto'case; In the newspaper. The purpose of this research is to know the meaning and function of the metaphor, this study also tries to find out the conceptualizations of politics. In this case, the author uses the theory of Lakoff and Johnson. Data were taken from 4 news from people's mind newspaper Tuesday 28 November 2017, Kompas daily pad Monday 20 November 2017, new compass on 22 November 2017 and people's mind on 20 November 2017 . in this research the writer use a qualitative research Method. Which all of the data are they presented descriptively. From the analysis, the result found 4 political discourses in conceptual metaphor in the newspaper about Setya Novanto cases. From 175 metaphorical statements, the researcher found 55 metaphors. that is found 45 % as objects or goods that can be traded.30 % politics as a battle,10% as a war and 15 % as a race. It shows that in the political discourses.Keywords: Newspaper, Conceptual, Metaphor, Setya Novanto’s case.